Psychosocial, physical, cognitive and quality of life aspects in primary restless legs syndrome - Jarašiūnaitė , I.; Kaladytė-Lokominienė, R. (Neurologijos seminarai, 2019)
Background. Restless Legs Syndrome (RLS) is a chronic neurological disorder manifesting with unpleasant sensations in the legs and/or other parts of the body and uncontrollable urge to move in order to reduce sensory discomfort. This syndrome affects 5-15% of the population worldwide. RLS has a significant impact on the quality of life. The syndrome is accompanied by nocturnal sleep disturbances and excessive daytime sleepiness. There is a number of studies on relationship between RLS and cognitive decline, however, their results are controversial. Materials and methods. The study took place from January to March 2019 in the Center of Neurology of Vilnius University Hospital Santaros Klinikos. It involved 19 patients with primary RLS and 20 age-, education- and sex- matched control volunteers without RLS. Participants of the study were provided with a questionnaire pack, including International RLS Study Group scale (IRLSSGS), demographic data, quality of life scale SF-36, Hospital Anxiety and Depression Scale (HADS), Montreal Cognitive Assessment (MoCA), Epworth daytime sleepiness scale, and Fatigue questionnaire. RLS group subjects underwent Timed Up-And-Go Test (TUG) with 10 m distance for evaluation of movement speed. Statistical analysis was performed with SPSS 23.0 program; Person’s correlation, chi² test, two sample t-test were used. Data was considered statistically significant at p<0.05. Results. The study included 39 participants (32 women) aged 65.1±11.3 years. There was a statistically significant difference in MoCA total score (p=0.007), attention (p=0.002) and delayed recall (p=0.005) subscores between subjects with RLS and control group. General health perception score by SF-36 questionnaire was significantly lower (p=0.032) in RLS group. A moderate negative correlation was found between IRLSSGS scores and the assessment of bodily pain (p<0.001, r=-0.694) and general health perception evaluation (p=0.009, r=-0.585). The result of TUG test did not correlate with IRLSSGS score (p=0.523, r=0.156). There was no statistically significant difference in HADS depression and anxiety scores (p=0.282 and p=0.219) and daytime sleepiness ant fatigue evaluation results (p=0.141 and p=0.109, respectively) between RLS and control groups. Conclusions. RLS severity is related to the worsening of quality of life (according to bodily pain and general health perception evaluation). RLS is not associated with higher levels of depression and anxiety. Results of evaluation of speed of movement are not related with severity of RLS. Results of cognitive testing of RLS patients are worse than in control group.